Spirit crossing : a novel - Krueger, William Kent (New York : Atria Books, 2024)
"The disappearance of a local politician$1 (Bs teenaged daughter is major news in Minnesota. As a huge manhunt is launched to find her, Cork O$1 (BConnor$1 (Bs grandson stumbles across the shallow grave of a young Ojibwe woman$1 (Bbut nobody seems that interested. Nobody, that is, except Cork and the newly formed Iron Lake Ojibwe Tribal Police. As Cork and the tribal officers dig into the circumstances of this mysterious and grim discovery, they uncover a connection to the missing teenager. And soon, it$1 (Bs clear that Cork$1 (Bs grandson is in danger of being the killer$1 (Bs next victim." --publisher's websites
Includes bibliographical references (page [321]).
Keywords: O'Connor, Cork (Fictitious character) -- Fiction; Indian reservation police -- Fiction; Children of politicians -- Crimes agains -- Fiction; Missing persons -- Investigation -- Fiction; Murder -- Investigation -- Fiction; Grandsons -- Protection -- Fiction; Indigenous peoples -- Fiction; Ojibwa women -- Death -- Fiction; Politicians -- Fiction; Detective and mystery stories; Detective and mystery fiction